Friendship as Method - Tillmann-Healy, Lisa M. (Qualitative inquiry, 2003)
In this article, the author discusses friendship as a method of qualitative inquiry. After defining friendship and positing it as a kind of fieldwork, the methodological foundations of friendship as method are established. Next, it is proposed that friendship as method involves researching with the practices, at the pace, in the natural contexts, and with an ethic of friendship. Finally, the author describes this method's strengths and considerations for both researcher and participants.